Peran Strategis NU (Nahdlatul Ulama) dalam Menopang Keberlanjutan Bangsa - Nurul Huda (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2024)
Nahdlatul Ulama (NU), as the largest Islamic organization in Indonesia, plays a strategic role in supporting the nation's sustainability across various dimensions, including social, educational, economic, and political aspects. Guided by the principle of Islam as rahmatan lil 'alamin (a mercy to all creation), NU is committed to fostering a civil society that is tolerant, inclusive, and just. This study aims to analyze NU's strategic role in ensuring national sustainability by focusing on the implementation of its flagship programs, the organization's leadership role, and its impact on national development. Furthermore, the study identifies the challenges faced by NU in navigating socio-political dynamics and globalization while offering strategic recommendations to optimize its contributions in the modern era. The findings of this study are expected to provide new insights for academics, practitioners, and policymakers on the critical role of faith-based organizations in supporting national sustainability.